22q11 microdeletion syndrome and ultra‐high risk for psychosis: The role of neurological soft signs as an independent marker of vulnerability for psychosis. Issue 5 (26th November 2018) - Pitzianti, Mariabernarda; Pontillo, Maria; Vicari, Stefano; Armando, Marco; Pasini, Augusto
Abstract : Aim: 22q11 microdeletion syndrome has an increased risk for psychosis, similar to subjects at ultra‐high risk for psychosis. Neurological soft signs are considered an endophenotype of psychotic disorders and a marker of vulnerability to Schizophrenia, consisting of overflow movements, dysrhythmia and speed of timed activities. To date, there are no studies that have evaluated the presence of the neurological soft signs in subjects with 22q11 microdeletion syndrome and there are a few studies that have analysed this issue in subjects at ultra‐high risk. Methods: We sought to measure neurological soft signs in these two conditions, compared to healthy controls and to analyse the possible correlation between neurological soft signs and positive/negative symptoms both in 22q11 microdeletion syndrome and ultra‐high‐risk groups. 54 drug‐naive patients (29 with 22q11 microdeletion syndrome and 25 at ultra‐high risk for psychosis) and 25 healthy controls were evaluated for neurological soft signs. Results: Both clinical groups showed a greater number of neurological soft signs compared to healthy control, although the two clinical groups did not differ for the number of neurological soft signs. Positive correlation between speed of timed activities and negative symptoms was found in subjects at ultra‐high risk. Conclusion: Neurological soft signs could represent a marker of atypical neurodevelopment in the two populations examined. Since we did not found a strong correlation between neurological soft signs and positive/negative symptoms, we suggest that neurological soft signs could be indicators of vulnerability to psychosis independent from the psychopathology.